What shapes cadets’ decisions? Factors influencing the choice of the Faculty of Medicine of the Military Medical Academy - Petrović, Aleksandar; Kostić-Stanković, Milica; Ignjatović, Marina (Vojnosanitetski pregled, 2025)
Background/Aim. To create an effective promotional strategy for the Medical Faculty of the Military Medical Academy (MF MMA), it is essential to understand why young people decide to enroll in this military higher education institution (MHEI). The aim of this study was to identify the key factors and examine their influence on cadets’ decisions to enroll in MF MMA. Methods. A cross-sectional study was conducted during the second semester of the 2023/2024 academic year with 121 participants (cadets and candidates for enrollment at the MF MMA). A qualitative phase, aimed at defining the research instrument, was implemented using the focus group method. Data collection was performed using an online questionnaire. Analysis was conducted using multiple linear regression. Results. The factors that have the greatest influence on cadets’ decisions to enroll in the MF MMA are: “cultural capital” (β = 0.260; р < 0.01), “physical culture” (β = 0.210; р < 0.05), “quality of military medical education” (β = 0.191; р < 0.05), “career” (β = 0.176; р < 0.05), and “status” (β = 0.171; р < 0.05). Conclusion. The results indicate that cadets’ decision to choose MF MMA is influenced by the combination of personal and institutional factors of a predominantly social nature. Candidates applying for enrollment at the MF MMA have strong personal affinities towards the profession of an army officer/military doctor, highly value the culture of the military organization, appreciate the educational offer of the MHEI, and recognize opportunities for professional and career development. These findings may contribute to defining the promotional strategy of MF MMA and ensure that the institution maintains a stable influx of high-quality and motivated candidates for education.